The Bear Tree and Other Stories from Cazenovia's History - Barnes, Erica; Emerson, Jason, 1975- (Book collections on Project MUSE., 2021)
""The Bear Tree and Other Stories from Cazenovia's History" examines and illuminates the unknown, unheralded, inaccurately told, and long-forgotten stories of Cazenovia, New York"--